(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This paper reviews the sex-gender notions from the limits and limitations imposed by the bio-power up to the post-gender, based on the pharmacopornographic theory proposed by the Spanish philosopher Beatriz Preciado. According to Preciado‟s approach, gender is a discursive device that challenges the standard conceptions of sexual otherness, and this idea is blended with some critical trends from contemporary cultural studies and post-structuralism.